2014 Semiconductor Thermal Measurement and Management Symposium (SEMI-THERM) 2014
DOI: 10.1109/semi-therm.2014.6892209
|View full text |Cite
|
Sign up to set email alerts
|

Direct actuation of small-scale motions for enhanced heat transfer in heated channels

Abstract: Flow-effected, enhanced heat transfer in a high aspect ratio rectangular mm-scale channel that models a segment of a high-performance, air-cooled heat-sink is characterized. The present investigation reports a novel approach to enhanced cooling without increasing the channel's characteristically low Reynolds number. Heat transport that is governed by the local heat transfer from the fin surface and by subsequent mixing with the core flow is significantly increased by deliberate shedding of unsteady small-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, for the tests conducted in a 5-channel heatsink, the heat transfer enhancement in Nusselt number varies between a minimum of 53% and a maximum of 69% at lower Reynolds number ranges. The test results shown by Hidalgo et al [17] reported that Nusselt number enhancement increases 43% at Re = 2000 to 88% at 5000 and the pressure drop increment increases from 37% at Re = 2000 to nearly 100% at Re = 4300. Both fluttering reed and AFA are passively driven by air flow through the fluid-structure-interaction process for inducing vortices within the channel to enhance the heat transfer coefficient at the heated wall surface.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, for the tests conducted in a 5-channel heatsink, the heat transfer enhancement in Nusselt number varies between a minimum of 53% and a maximum of 69% at lower Reynolds number ranges. The test results shown by Hidalgo et al [17] reported that Nusselt number enhancement increases 43% at Re = 2000 to 88% at 5000 and the pressure drop increment increases from 37% at Re = 2000 to nearly 100% at Re = 4300. Both fluttering reed and AFA are passively driven by air flow through the fluid-structure-interaction process for inducing vortices within the channel to enhance the heat transfer coefficient at the heated wall surface.…”
Section: Introductionmentioning
confidence: 97%
“…However, for the experiments tested in a 5-channel plate-fin heatsink, the heat transfer augmentation in global Nusselt number varies from 53% to 69% at lower Reynolds number ranges. The test results presented by Hidalgo et al [17] reported that averaged Nusselt number augmentation increases 43% at = 2000 to 88% at = 5000 and the pressure drop increment arises from 37% at = 2000 to nearly 100% at = 4300. Jha and et al…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations